2017
DOI: 10.1016/j.exer.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinal levels and formation of lipofuscin precursors after bleaching in rod photoreceptors from wild type and Abca4 mice

Abstract: The accumulation of lipofuscin in the cells of the retinal pigment epithelium (RPE) is thought to play an important role in the development and progression of degenerative diseases of the retina. The bulk of RPE lipofuscin originates in reactions of the rhodopsin chromophore, retinal, with components of the photoreceptor outer segment. The 11-cis retinal isomer is generated in the RPE and supplied to rod photoreceptor outer segments where it is incorporated as the chromophore of rhodopsin. It is photoisomerize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
4
5
0
1
Order By: Relevance
“…8). This makes it unlikely that LFPs originate from free-dwelling all-trans-retinal, and it is consistent with the suggestion that they form from all-trans-retinal trapped in the form of a Schiff base with phosphatidylethanolamine (10). Another possibility would be that a small amount of chromophore remains trapped in aggregated opsin within which the Schiff base is retained.…”
Section: All-trans-retinal and Retinol Clearance By Irbpsupporting
confidence: 77%
See 2 more Smart Citations
“…8). This makes it unlikely that LFPs originate from free-dwelling all-trans-retinal, and it is consistent with the suggestion that they form from all-trans-retinal trapped in the form of a Schiff base with phosphatidylethanolamine (10). Another possibility would be that a small amount of chromophore remains trapped in aggregated opsin within which the Schiff base is retained.…”
Section: All-trans-retinal and Retinol Clearance By Irbpsupporting
confidence: 77%
“…Accumulation of all-trans-retinal due to metabolic limitations has been shown to result in excess formation of LFPs in rod photoreceptor outer segments (10). All-trans-retinal also accumulates in Rdh8 Ϫ/Ϫ rod outer segments, which lack the enzyme needed for the reduction of retinal to retinol (3,48,50).…”
Section: All-trans-retinal and Retinol Clearance By Irbpmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of our recent study suggested that moderate photoreactivity of BRex not subjected to oxidation, could be attributed hydrophobic endogenous sensitizers present in Folch’ extracts of neural retinas. One of these sensitizers is all‐trans retinal (atRAL), a product of photobleaching of the visual pigment rhodopsin, which may temporarily accumulate in POS . It has previously been shown that atRAL generates 1 O 2 with quantum yield about 0.3 .…”
Section: Resultsmentioning
confidence: 99%
“…One of these sensitizers is all-trans retinal (atRAL), a product of photobleaching of the visual pigment rhodopsin, which may temporarily accumulate in POS. [11,38] It has previously been shown that atRAL generates 1 O 2 with quantum yield about 0.3. [39] Not oxidized BRex may contain small amounts of atRAL, which could contribute to generation of singlet oxygen by the photoexcited LUV prepared from not oxidized BRex (0 h).…”
Section: Phagocytosis Assay and Flow Cytometry Analysismentioning
confidence: 99%